2016
DOI: 10.1519/jsc.0000000000001268
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lower Extremity Muscle Size and Quality on Stair-Climb Performance in Career Firefighters

Abstract: The purpose of this study was to examine the influence of lower extremity muscular size and quality on stair-climb performance (SCP) in career firefighters. Forty-six male career firefighters (age = 37.0 ± 7.2 years; stature = 180.2 ± 6.9 cm; body mass = 108.0 ± 19.8 kg) volunteered for this study. Panoramic ultrasound images of the vastus lateralis and rectus femoris were obtained to determine cross-sectional area (CSA) and echo intensity (EI) of each muscle. The CSA of each muscle was then summed together an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
42
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 25 publications
6
42
1
2
Order By: Relevance
“…Removing the influence of age and mass eliminated the significant correlation between VL muscle thickness and peak torque, but not RTD100 or RTD200. These findings are consistent with the growing body of literature that shows significant correlations between lower‐extremity muscle quality and quantity versus physical function in adults …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Removing the influence of age and mass eliminated the significant correlation between VL muscle thickness and peak torque, but not RTD100 or RTD200. These findings are consistent with the growing body of literature that shows significant correlations between lower‐extremity muscle quality and quantity versus physical function in adults …”
Section: Discussionsupporting
confidence: 91%
“…Echo intensity and muscle thickness are used increasingly in adult studies to examine muscle quality and quantity, respectively. The results of our study are consistent with those that have demonstrated significant relationships between these variables and physical function . Of interest, in older women, quadriceps femoris echo intensity obtained by means of ultrasonography provided better predictive information concerning peak torque and functionality than the actual ratio of muscle strength to size .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations